Emosi dan Tindakan Tokoh Utama dalam Roman Poil De Carotte Karya Jules Renard: Sebuah Kajian dari Teori Emosi James-Lange - Widawati, Naning; Sunahrowiï€ª, Sunahrowiï€ª (Lingua Litteria Journal, 2021)
The study entitled "The Emotions and Actions of the Main Character in Jules Renard's novel Poil de Carotte: A Study of James-Lange Theory of Emotions" aims to describe the violent emotions and actions of the main character in the novel of Poil de Carotte. The data used in this study was a novel entitled Poil de Carotte by Jules Renard. This study used James-Lange theory of emotions. The data analysis method used in this research was descriptive analytic method, while the analysis technique used in this research was content analysis technique. The result of this study are the rough emotions produced by the main character Poil de Carotte such as pride, hate, sadness, happiness, fear, love, anger, and disappointment. Meanwhile, the result of action was the character of Poil de Carotte experienced emotions of hatred, anger, fear, and disappointment.